Contemplative and Transformative Learning for Character Development in Islamic Higher Education - Ade Alimah (Universitas Islam Negeri Mataram, 2020)
Islamic higher education is supposed to develop Indonesians' characters due to its focus on teaching Islam. Moreover, the number of Islamic higher education institutions is vast, reaching 777. Indeed, their contribution to the character development of Indonesians may be significant. However, occurring religious-based prejudices and conflicts, as well as a high index of corruption, show the paradoxes and challenges of Islamic higher education. Although there has been no research demonstrating a statistically significant correlation between Islamic teaching and crime rate or moral issues, educators in Islamic higher education institutions should reflect on what should be done to enhance their leverage on character education. In this paper, two concepts of contemplative learning and transformative learning are discussed to find feasible ways of teaching Islam in the challenging contemporary world. Contemplative and transformative learning in character development requires educators to implement mindfulness and connectedness through integrating all entities of learners' cognition, emotion, intuition, and body, interrelating multi-disciplines, and connecting learning to the real world.